Soft-start circuit with duty ratio controlled voltage clamping and adaptive sizing technique for integrated DC-DC converters - Xiaocheng Jing; Mok, Philip K T (2010 IEEE International Conference of Electron Devices and Solid-State Circuits, 2010)
A novel soft-start technique with charge-pump based staircase clamping voltage generator to eliminate the inrush-current and over-shoot voltage is presented. Proper duty cycle is introduced as a new freedom to control the soft-start speed which enables a fully on-chip design to reduce the cost of the converter. In addition, adaptive sizing method is presented to control the charging current for boost converters when the output voltage is less than the input voltage. A boost DC-DC converter is implemented with a 0.35 μm CMOS process. Simulation results show a smooth start-up with load range from 0-500 mA.